2014
DOI: 10.1021/jp504923x
|View full text |Cite
|
Sign up to set email alerts
|

Polaron Structure and Transport in Fullerene Materials: Insights from First-Principles Calculations

Abstract: Organic semiconductors offer a low-cost alternative to inorganic semiconductors. However, their usefulness is limited by a relatively low mobility of polaron charge carriers. Past research indicates a positive correlation between charge density and charge mobility in organic semiconductors. This relationship is usually attributed to the phenomenon of excess charges filling traps. Here, we explore whether charge density may also affect mobility via influence on intermolecular couplings. Density functional theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Previous work has shown that OPV performance is affected by the relative orientation of donor and acceptor molecules, 123,124,146,211 and charge transport in organic semiconductors is known to be sensitive to small changes in intermolecular orientation. 25,26,212,213 This sensitivity to small changes in orientations is consistent with reports that changes in phase, such as aggregation into a mixed phase, cause changes in excitation energies for both polymers and fullerenes in OPV materials. 142,[214][215][216][217] EPR studies have shown that the electronic structure of C 60 anions is sensitive to geometric distortions, consistent with the sensitivities to geometry that we observe in organic semiconducting devices.…”
Section: Density Functional Theorysupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work has shown that OPV performance is affected by the relative orientation of donor and acceptor molecules, 123,124,146,211 and charge transport in organic semiconductors is known to be sensitive to small changes in intermolecular orientation. 25,26,212,213 This sensitivity to small changes in orientations is consistent with reports that changes in phase, such as aggregation into a mixed phase, cause changes in excitation energies for both polymers and fullerenes in OPV materials. 142,[214][215][216][217] EPR studies have shown that the electronic structure of C 60 anions is sensitive to geometric distortions, consistent with the sensitivities to geometry that we observe in organic semiconducting devices.…”
Section: Density Functional Theorysupporting
confidence: 90%
“…[19][20][21][22][23] for more detailed discussion of exciton diffusion in OPVs and ref. [24][25][26][27][28] for more discussion of charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated organic polymers, which exhibit a good absorption and emission of light or electricity and photoconductivity, have been widely used in electronic devices such as organic eldeffect transistors (OFETs), 1,2 organic light emitting diodes (OLEDs) 3,4 and organic photovoltaic devices (OPVs). [5][6][7] Compared with the traditional inorganic semiconductor materials, the conjugated organic polymers have many outstanding advantages, such as being low-cost, exible, lightweight materials and having a large-area fabrication. All these merits increase their applicability as active components in organic electronic devices and molecular electronics.…”
Section: Introductionmentioning
confidence: 99%
“…The geometries, electronic structures, polarizabilities and hyperpolarizabilities, and UV-vis spectra of metallo phthalocyanine dyes and metallophthalocyanine-fullerene supramolecules were studied [ 16 ]. The relationship between charge density and mobility of fullerenes was revealed by using first-principles calculation [ 17 ]. Barszcza et al .…”
Section: Introductionmentioning
confidence: 99%